Interferon in systemic lupus erythematosus—A halfway between monogenic autoinflammatory and autoimmune disease. Issue 11 (November 2022) - Saulescu, Ioana; Ionescu, Ruxandra; Opris-Belinski, Daniela
Abstract: Although perceived as an adaptative immune disorder, mainly related to Lymphocyte B and T, last years focus on Systemic Lupus Erythematosus (SLE) pathogeny emphasised the important role of innate immunity. This should not take us by surprise since the lupus cell described by Hargraves and colleagues in 1948 was a neutrophil or macrophage with specific aspect after coloration with haematoxylin related to cell detritus engulfment (Hargraves et al., 1948) [1] ( Presentation of two bone marrow elements; the tart. Hargraves M, Ricmond H, Morton R. 1948, Proc Staff Meet Mayo Clinic, pp. 23:25–28). Normal immune system maintains homeostasis through innate and adaptative response that are working together to prevent both infection and autoimmunity. Failure of the immune mechanisms to preserve the balance between these two will initiate and propagate autoinflammation and/or autoimmunity. It is well known now that autoinflammation and autoimmunity are the two extremes of different pathologic conditions marked with multiple overlaps in many diseases. Recent findings in SLE demonstrated that innate immune system initiates the abnormal autoimmunity and starts the continuous inflammatory reaction after that, interferon being one of the key cytokines in innate immunity and SLE. Understanding this mechanism might offer a better clue for an efficient treatment in SLE patients. The purpose of this review is to highlight the enormous impact of innate immunity and mostly interferons in SLE. Abstract : Interferon; Systemic lupus erythematosus; Toll like receptor; Interferonopathies; Autoimmunity; Autoinflammation.